The biosimilars journey: current status and ongoing challenges - Igor Age Kos; Valderílio Feijó Azevedo; Daniel Egg Neto; Sérgio Cândido Kowalski (BioExcel Publishing Ltd, 2018)
Biosimilar products are already approved and marketed in several countries. The Food and Drug Administration has approved ten different biosimilars, and the European Medicines Agency has approved 40. Even though this scenario has provided important experience with biosimilar products, there are still challenges and unanswered questions. Up to now, a good amount of knowledge has been gathered in order to support the importance of the totality of evidence and the construction of a biosimilarity exercise for regulatory approval. In addition, the extrapolation of indications has been proved viable when a careful analysis is performed. The models for clinical trials and the use of the most sensible populations have been extensively discussed, and there is apparent homogeneity in manufacturer choices for study designs. However, some challenges remain. The lack of regulatory harmony, especially concerning naming, the marketed intended copies, the interchangeability, and the biosimilars in orphan diseases are some of those and are the focus of discussion in this review.